Odpowiedzi

Najlepsza Odpowiedź!
2010-04-15T16:13:54+02:00
A)(4x + 5y = -4 ]* (-3)
(6x + 7y = -6 ]*2

(-12x -15y =12
(12x +14y=-12
+________________
-y=12
y=-12

4x + 5y = -4
4x - 60 =-4
4x= 56
x= 14


b)(2x - 11y = 73 ]*(-3)
(3x - 4y = 47 ]*2

(-6x +33y = -219
(6x -8y =94
+________________
25y=- 125 ] ÷ 25
y=-5

3x - 4y = 47
3x +20 = 47
3x=27 ]:3
x=9



c)(-2x + 5y = -10 ]*7
(7x - 4y = 8 ]*2

(-14x +35y= -70
(14x-8y =16
+_______________
27y= -54
y=-2

7x - 4y = 8
7x +8 =8
x=0



d) (9x + 8y = 1 ]*3
(5x - 6y = 11 ]*4

(27x + 24y= 3
(20x -24y = 44
+__________________
47x = 47
x=1

9x + 8y = 1
9+8y= 1
8y= -8
y= -1